Determining quality of service in IEEE 802.11 multi-hop adhoc networks through end user perception - Giyane, Maxmillan; Zhou, Munyaradzi (Midlands State University, 2014)
This paper seeks to determine Quality of Service (QoS) in the transmission of multimedia traffic in Institute of Electrical and Electronics Engineers (IEEE) 802.11 multi-hop ad hoc networks as perceived by the end user in a simulated setup using NS-2 and EvalVid framework. Extensive simulations indicated that the QoS provision is a challenging task in multi-hop ad hoc networks. QoS is perceptible when the following QoS metrics are very low; delay, jitter, packet loss, frame loss and also when error rate is very low. Increased mobility, network size, packet loss and delay adversely affect QoS. Due to the rapid deployment of multimedia applications, network practitioners, network researchers and the telecommunication industry will gain insight in evaluating their network designs or setup as perceived by users.